An Analytical study of Rainfall characteristics over Wayanad District of Kerala - et. al., Varuna Madhu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the major problems before the scientific community is to tackle the climate change issues around the world. Kerala is one such state of India where impact of climate changes can be evidently observed. In this study, climate change footprints are evaluated using different statistical techniques over three regions of Wayanad viz. Mananthavady, Vythiri and Kuppady from 1999 to 2014. The results suggest that the rainfall over these regions have become asymmetric with contribution of September month rainfall increasing while other month decreasing which clearly indicates the change in the rainfall distribution over these regions. Also, the maximum change is observed in the Kuppady region with an increase of 29 mm/year of rainfall, whereas decrease in rainfall is found in Mananthavady and Vythiri. Hence, this study indicates significant changes in rainfall in monthly as well as seasonal scale in different parts of Wayanad, Kerala.